2016
DOI: 10.1007/s12098-016-2099-x
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis in South Indian Centre

Abstract: A female preponderance, less familial clustering, higher paucity of clinical manifestations and quick progression to hypothyroidism (in those without) were noted in the present series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Diagnosis of HT was based on the classic criteria: Presence of thyroid peroxidase (TPO) antibody and/or thyroglobulin (TG) antibody, associated with primary hypothyroidism. [11] Free T4 and thyroid-stimulating hormone (TSH) were measured by electrochemiluminescent (Elecsys FT4) assay using a specific anti T4 antibody labeled with a ruthenium complex (limits of detection: 0.5 pmol/L-100 pmol/L) and monoclonal antibody directed against human TSH (0.005 µIU/mL-100 µIU/mL) using Cobas e411 analyzer, respectively. Anti-TPO antibody and anti-TG antibody were measured by electrochemiluminescent immunoassay using a recombinant antigen with polyclonal anti-TPO antibody (limits of detection: 5-600 IU/mL) and human antigen and monoclonal anti-TG antibody (limits of detection: 10-4000 IU/mL), respectively, using Cobas e411 analyzer; test number 720.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of HT was based on the classic criteria: Presence of thyroid peroxidase (TPO) antibody and/or thyroglobulin (TG) antibody, associated with primary hypothyroidism. [11] Free T4 and thyroid-stimulating hormone (TSH) were measured by electrochemiluminescent (Elecsys FT4) assay using a specific anti T4 antibody labeled with a ruthenium complex (limits of detection: 0.5 pmol/L-100 pmol/L) and monoclonal antibody directed against human TSH (0.005 µIU/mL-100 µIU/mL) using Cobas e411 analyzer, respectively. Anti-TPO antibody and anti-TG antibody were measured by electrochemiluminescent immunoassay using a recombinant antigen with polyclonal anti-TPO antibody (limits of detection: 5-600 IU/mL) and human antigen and monoclonal anti-TG antibody (limits of detection: 10-4000 IU/mL), respectively, using Cobas e411 analyzer; test number 720.…”
Section: Methodsmentioning
confidence: 99%
“…[9] A recent Indian study has demonstrated that thyroxine therapy for 6 months results in advancement of skeletal maturity by 11 months. [10] Although there are Indian studies on prevalence of HT in children, [2,11] there are no studies describing the impact of therapy on final height potential. Hence, we conducted this study with an aim to determine whether delayed diagnosis of primary hypothyroidism due to HT has an impact on catch-up growth of children and adolescents.…”
Section: Journal Of Pediatric Endocrinology and Diabetesmentioning
confidence: 99%
“…The incidence of HT has a rapid growth in the last 3 decades and is 0.3–1.5 persons per 1000 individuals [ 4 , 5 ]. HT could be divided into different types including euthyroid HT, subclinical hypothyroidism, overt hypothyroidism, or hyperthyroidism based on the thyroid function [ 6 , 7 ].…”
Section: Introduction Backgroundmentioning
confidence: 99%